Immunomodulatory potential effects of pomegranate peel in the immunization of chickens against Newcastle disease virus - Ebrahimi, MM; Motamed, N; Shahsavandi, S (Journal of the Hellenic Veterinary Medical Society, 2025)
Newcastle disease (ND) is an acute, transmissible, infectious respiratory disease associated with high mortality and morbidity in chickens. Biosecurity, mass vaccination, and improved immunization are suggested as controlling strategies. Enhancing poultry’s innate immunity using natural feed additives eventually activates adaptive immune responses. This research was conducted to determine the effect of a diet supplemented with pomegranate peel (Pop) on the immune status of chickens whether vaccinated against NDV or not. Pop antioxidant capacity was determined by calculating radical scavenging activity. Specific pathogen-free (SPF) chickens’ basal diet was supplemented with 1.0% Pop. Chickens were divided into four groups (A-D; n=20): (A) NDV vaccination + basal diet; (B) NDV vaccination + Pop feeding; (C) Pop feeding; and (D) control. Day-old chicks were vaccinated against NDV with a booster dose at 14 days of age. The experimental trial lasted 42 days. Kinetics of IFN-γ and chTLR4 immune response gene expressions and nitric oxide production levels were assessed in primary chicken monocyte-derived dendritic cells isolated from the chicken groups. Humoral and cell-mediated immune responses were also evaluated. Upregulating IFN-γ and chTLR4 expression in the Pop-feeding groups suggested a significant increase in the innate immunity of chickens. The chickens also showed a marked decrease in nitric oxide production levels, which could be attributable to Pop’s high total antioxidant capacity. Slight increases in humoral and lymphoproliferative responses against NDV confirmed the synergistic effect of Pop. These findings suggest that Pop potentiated the immunomodulatory impact on chicken’s innate immunity and acted synergistically on adaptive immunity against NDV.